Impact of Weight Loss on Physical Function with Changes in Strength, Muscle Mass, and Muscle Fat Infiltration in Overweight to Moderately Obese Older Adults: A Randomized Clinical Trial - Adam J. Santanasto; Nancy W. Glynn; Mark A. Newman; Christopher A. Taylor; Maria Mori Brooks; Bret H. Goodpaster; Anne B. Newman (Hindawi Limited, 2011)
Purpose. Evaluate the effects of weight loss on muscle mass and area, muscle fat infiltration, strength, and their association with physical function. Methods. Thirty-six overweight to moderately obese, sedentary older adults were randomized into either a physical activity plus weight loss (PA+WL) or physical activity plus successful aging health education (PA+SA) program. Measurements included body composition by dual-energy X-ray absorptiometry, computerized tomography, knee extensor strength, and short physical performance battery (SPPB). Results. At 6 months, PA+WL lost greater thigh fat and muscle area compared to PA+SA. PA+WL lost 12.4% strength; PA+SA lost 1.0%. Muscle fat infiltration decreased significantly in PA+WL and PA+SA. Thigh fat area decreased 6-fold in comparison to lean area in PA+WL. Change in total SPPB score was strongly inversely correlated with change in fat but not with change in lean or strength. Conclusion. Weight loss resulted in additional improvements in function over exercise alone, primarily due to loss of body fat.